2018
DOI: 10.17576/ajag-2018-10-07
|View full text |Cite
|
Sign up to set email alerts
|

The effect of earnings management on bank efficiency

Abstract: A study on the effects of earnings management practices on bank cost efficiency, using banking data in five ASEAN countries, was conducted in 1989-2015. The Stochastic Frontier Analysis technique employed to gauge cost efficiency revealed that each country has different efficiency level. With panel data analysis, we further discovered that increase in earnings management practices reduces bank's efficiency significantly. It is suggested that banking supervisors and managers should formulate strategies that foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…Their study focused on the effect of earnings management on the efficiency of Eurozone banks using a sample of 70 banks under the supervision of the European Central Bank. A similar result was obtained in the study of Ab-Hamid, Asid, Sulaiman, Sulaiman, and Bahri (2018) on the impact of earnings management on the efficiency of banks in five Association of Southeast Asian Nations (ASEAN) countries.…”
Section: Empirical Reviewsupporting
confidence: 83%
See 1 more Smart Citation
“…Their study focused on the effect of earnings management on the efficiency of Eurozone banks using a sample of 70 banks under the supervision of the European Central Bank. A similar result was obtained in the study of Ab-Hamid, Asid, Sulaiman, Sulaiman, and Bahri (2018) on the impact of earnings management on the efficiency of banks in five Association of Southeast Asian Nations (ASEAN) countries.…”
Section: Empirical Reviewsupporting
confidence: 83%
“…Notably, regarding corporate governance, studies by Ebimobowei (2022), Marie et al (2021), andKhanifah et al (2020) documented positive significant effects, while studies by Ali et al (2020), Omesi and Appah (2021), and Boshnak (2021) reported negative effects. On the other hand, studies on financial reporting by Ayuba (2022); Aguguom et al (2019), Proença et al (2023), Ab-Hamid et al (2018), and Fonou-Dombeu et al (2022 reported mixed findings. These divergences further suggest inclusiveness and create gaps for further research.…”
Section: Empirical Reviewmentioning
confidence: 97%
“…These attributes are arguably dissimilar to those in advanced economies, which was the focus of prior EM studies. Contrastingly, different from prior Malaysian EM studies (Ab-Hamid et al 2018;Abdul Rahim & Nelson 2018), this study uses a multiple regression method on 227 Malaysian listed firms from 2001-2015 and finds firms that just meet the earnings benchmark (avoid losses and earnings decline), either via accrual and real earnings management activities, have lower future performance. Furthermore, if these firms managed earnings via real earnings management (REM) to just meet the earnings benchmark will have an even lower future performance.…”
Section: Introductionmentioning
confidence: 93%
“…Manajemen laba di bank dilakukan berdasarkan provisi kerugian pinjaman diskresioner dan keuntungan keamanan dan kerugian untuk mengelola laba dan tingkat modal (Hamid et al, 2018). Praktik manajemen laba dapat mengganggu kemampuan bank untuk menggunakan alokasi sumber daya secara optimal saat menawarkan layanan perantara keuangan mereka.…”
Section: Literature Review Manajemen Labaunclassified